ENMTML: An R package for a straightforward construction of complex ecological niche models. (March 2020) - Andrade, André Felipe Alves de; Velazco, Santiago José Elías; De Marco Júnior, Paulo
Abstract: Ecological niche models (ENMs) is a popular method in ecology, mostly due to its broad applicability and the fact that required data is simple and easily accessible from digital databases. Nevertheless, there is an underlying methodological complexity, often overlooked by many scientists that rely on ENMs to achieve other objectives. We present here the package ENMTML, an Open Source R package. The main purpose of this package is to assemble all this methodological complexity spread over several papers and bring it into the spotlight in a simple way for people not used to the details of ENMs. The package contains several alternatives to different methodological steps, e.g., pseudo-absence allocation and accessible area delimitation, formulated within a single function, to make it accessible for people not used to the programming environment. Highlights: We present ENMTML, an open source R package to fit ecological niche models (ENMs). The package covers a wide variety of methodological aspects gathered from several studies. Complex methodological features, which were not readily available in R, are now easily accessible to users. We condense all this complexity in a single function to make it easier for users to follow a workflow. We demonstrate an example of fitting models for four species with complex methodological choices and its interactions.